Efficient and Thermally Stable All‐Perovskite Tandem Solar Cells Using All‐FA Narrow‐Bandgap Perovskite and Metal‐oxide‐based Tunnel Junction. Issue 48 (30th October 2022) - Wu, Pu; Wen, Jin; Wang, Yurui; Liu, Zhou; Lin, Renxing; Li, Hongjiang; Luo, Haowen; Tan, Hairen
Abstract: Commercialization of all‐perovskite tandem solar cells requires thermally stable narrow‐bandgap (NBG) perovskites and tunnel junction. However, the high content of methylammonium (MA) and organic hole transport layer used in NBG perovskite subcell undermine the thermal stability of all‐perovskite tandems. Here, thermally stable mixed lead‐tin NBG perovskite solar cells (PSCs) are developed by using only formamidinium (FA) for the A‐site cation. Solution‐processed indium tin oxide nanocrystals (ITO NCs) are deployed further to replace the conventional organic charge transport layer. Meanwhile, the ITO NCs layer simultaneously functions as a recombination layer in the tunnel junction, which simplifies the architecture of all‐perovskite tandem devices. The thermally stable all‐FA Pb‐Sn PSCs achieve a high power conversion efficiency (PCE) of 21.0%. With the thermally stable all‐FA NBG perovskite and optimized tunnel junction, a stabilized PCE of 26.3% is further obtained in all‐perovskite tandems. The unencapsulated tandem devices maintain >90% of their initial efficiencies after 212 h aging at 85 °C in the N2 atmosphere. The strategies herein offer a crucial step toward efficient and thermally stable all‐perovskite tandem solar cells. Abstract : Commercialization of all‐perovskite tandem solar cells requires both, a thermally stable narrow‐bandgap perovskite and a tunnel junction. Here all‐FA Pb‐Sn perovskite with superior intrinsic thermal stability and metal‐oxide‐based tunnel junction are deployed synchronously, which resulted in a power conversion efficiency of 26.3% and much improved thermal stability in all‐perovskite tandem solar cells.